2009
DOI: 10.1002/clc.20665
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Transluminal Angioplasty and Stenting for Pulmonary Stenosis Due to Takayasu's Arteritis: Clinical Outcome and Four‐year Follow‐up

Abstract: Background: Percutaneous transluminal angioplasty and stent implantation for stenotic lesions of renal arteries and other branches of the aorta in Takayasu's arteritis have been reported to show good outcomes. However, this form of therapy has been reported in few cases with pulmonary artery involvement. Hypothesis: The aim of this study was to evaluate the role of this interventional treatment for pulmonary stenosis due to Takayasu's arteritis. Methods: A total of 4 patients (3 female and 1 male, ages 30-40 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 17 publications
0
40
0
1
Order By: Relevance
“…Qin et al reported their experience in the management of four patients with pulmonary artery stenosis due to TA using percutaneous transluminal balloon angioplasty and stenting. The authors reported immediate success in all four cases and sustained relief in three patients in 4‐year follow‐up . Another report highlights successful management of a 45‐year‐old female patient with total occlusion of the RPA and significant stenosis of the LPA by surgical bypass grafting of the affected segment .…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Qin et al reported their experience in the management of four patients with pulmonary artery stenosis due to TA using percutaneous transluminal balloon angioplasty and stenting. The authors reported immediate success in all four cases and sustained relief in three patients in 4‐year follow‐up . Another report highlights successful management of a 45‐year‐old female patient with total occlusion of the RPA and significant stenosis of the LPA by surgical bypass grafting of the affected segment .…”
Section: Discussionmentioning
confidence: 88%
“…Although involvement of pulmonary arteries is not uncommon in TA, it often accompanies aortic involvement. Isolated stenosis of pulmonary artery branches as an initial manifestation is rarely encountered with only few published reports . It is commonly diagnosed after remarkable progression due to low clinical suspicion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical therapies, including angioplasty, stenting, bypass, and even pulmonary artery replacement, have been reported to manage pulmonary artery stenosis in TA. 94,95 Generally, surgical interventions should only be undertaken once the disease is quiescent, and even then restenosis is common.…”
Section: Behçet Syndromementioning
confidence: 99%
“…where r 0 is the initial radius and g r is used for changing rate. Clinical observations indicate that the resistance develops slowly and the progress may take years [19]. So, the time variable t in Eq.…”
Section: Model Of Nonlinear P-v Relation For Distal Pulmonary Arteriesmentioning
confidence: 99%